Sulfur-vulcanized CoFe2O4 with high-efficiency photo-to-thermal conversion for enhanced CO2 reduction and mechanistic insights into selectivity - Xiaoke Chen; Ming Cai; Pengwei Huo; Yan Yan; Yue Zhang; Pengxin Li; Zhi Zhu (Carbon Capture Science & Technology)
Semiconductor photocatalysts often exhibit low CO2 reduction activity due to inherent limitations. Photothermal (PTT) processes have emerged as crucial for enhancing this activity, yet investigations in this area remain sparse. This study introduces a novel CoFe2O3.5S0.5 photothermal catalyst, synthesized via hydrothermal methods with particle sizes ranging from 5 to 10 nm. Comparative analysis reveals that the CO yield from the as-prepared catalyst surpasses that of CoFe2O4 by 8.9 times, achieving 100% selectivity. The integration of sulfur significantly boosts near-infrared light absorption and promotes the conversion of light to thermal energy, enabling the catalyst to reach 185 °C within 300 ss. This rapid temperature escalation facilitates the swift separation of charge carriers. Additionally, the adsorption of CO2 and the dynamics of surface intermediates were thoroughly examined using in situ FTIR spectroscopy and theoretical models, identifying COOH* as the pivotal intermediate and the bottleneck in the reaction pathway. Our findings rectify gaps in prior studies and offer a foundational reference for further exploration of product selectivity in the photocatalytic reduction of CO2.